“I feel more confident in myself and my decision”: A study on the lived experiences of family approval among emerging adult Black women - Benjamin, Preshous (My University, 2025)
An impactful and brave milestone is solidifying a long-term relationship and choosing to introduce them to one’s family of origin. Family approval when introducing a new romantic partner is a phenomenon that has been captured in limited contexts. Although these contexts are important, it can be helpful to see how family approval can impact Black women emerging adults. As this population is in the process of shifting into a new phase of life as a couple, it is worth observing how they manage this transition and family approval while engaging in committed relationships. An interpretive phenomenological approach allowed the researcher to achieve this goal. Life course theory was the leading theory of this study. The sample included nine emerging adults aged 24-29 who are in a committed relationship and have experienced some form of family approval. It was found that emerging adults can have a positive experience if transparent communication is present and their confidence in their decision-making is increased, further creating a positive experience in the stage of emerging adulthood. Clinical and research implications are also presented.
Keywords: Black women; Family approval; Emerging adulthood; Qualitative